PENGARUH SUPERVISI DAN MOTIVASI INTRINSIK TERHADAP KREATIVITAS GURU SD SWASTA KATOLIK DI JAKARTA TIMUR - Ni Made Wiryanti (Universitas Negeri Jakarta, 2017)
The objective of this research was to understand the effect of supervision and intrinsic motivation to the crativity of private catholic elementary schools teachers in east Jakarta. The research uses a survey method with path analysis was applied in testing hypothesis. It was conducted to 187 teachers at Private Catholic Elementary Schools as the respondents which were selected by random sampling technique. The result of the research as follows: (1). Supervision of a positive direct effect on crativity, (2). Intrinsic motivation positive direct effect on creativity and (3). Supervision positive direct effect on intrinsic motivation .